Outcome of Pituitary Adenoma Surgery Through Transphenoidal Microscopic Approach : A Study of 15 Cases - Nath, Haradhan Deb; Barua, Kanak Kanti; Das, Malay Kumar; Bari, Shahnewaz (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Transphenoidal microscopic approach is minimally invasive surgery in case of pituitary adenoma. Comparatively less complication than transcranial approach. Objective: The purpose of the study to see the outcome of transphenoidal microscopic removal of pituitary adenoma. Results: The study showed the majority 8(53.33%) of patients were female. It was documented that 7(46.66%) of patient had age group 21-40 years. It was evident that 13(86.66%) of patient had macroadenoma. Among the 15 patients 14(93.33%) had visual disturbance and 1(6.64%) had pituitary apoplexy. Tumor was totally removed under microscope in 10(66.67%) cases. It was documented that 12(80.11%) of patients improved after surgery. Conclusion: Transphenoidal microscopic pituitary surgery is one of the important procedure which can save many lives with lack of postoperative complication. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 38-42